Peanuts. Happy holidays [videorecording (DVD)] - Schulz, Charles M. (Charles Monroe), 1922-2000 (Warner Bros., 2019)
The holidays are a time for family, laughter, and Peanuts! The gift of Charles Schulz's timeless comic strips come to life in this collection of 26 animated shorts. Whether it's the arrival of The Great Pumpkin, Old St. Nick, or the love-filled air of Valentine's Day, it's always the season of joy and friendship when Charlie Brown, Snoopy, and the rest of the gang are here.